Perbedaan konsumsi buah dan sayur pada anak sekolah dasar yang obes dan tidak obes di Kota Yogyakarta dan Kabupaten Bantul - Irma Nuraeni; Hamam Hadi; Yhona Paratmanitya (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2013)
ABSTRACTBackground: Curently, Indonesia has double burden problems nutrition, such as malnutrition and over nutrition. Overnutrition or obesity are not just happening in adults only, but also can occur in childhood. If the problem of obesity in children and adolescents cannot be resolved, it can be inﬂ uenced obese in adulthood then potentially to have noncommunicable diseases, such as cardiovascular disease, hypertension and diabetes mellitus. Prevalence of obesity inchildren at Yogyakarta Province increases year by year (1;2). Obesity was caused by an imbalance in energy intake andenergy expenditure. Children tend to consume high energy-dense, sweet  taste meal, high fat foods and less dietary ﬁber from fruits and vegetables. Several studies showed that there was increasing in risk of obesity from someone who have less consumption of fruits and vegetables.Objective:To determine differences in frequency and amount of fruit and vegetable consumption in elementary school children obese and non-obese at Yogyakarta Municipality and  District of Bantul and to ﬁnd out the risk of obesity in children who have less consumption of fruits and vegetables. Methods:The study design was a case-control, 244 samples as cases (obese children) and 244 controls (non-obesechildren). The subject of this study was children aged 6-12 years who were seated in class 1 to class 5 elementary schools at Yogyakarta Municipality and District of Bantul. Identity data obtained from a structured questionnaire respondent, frequency and amount of fruit and vegetable consumption were taken from Semi Quantitative Food Frequency Questioner(SQFFQ).Then the results analyzed using statistical test.Results: Statistical test showed that there were signiﬁcant differences (p<0,05) in the frequency and number of fruit and vegetable consumption in obese and non-obese elementary school children at Yogyakarta Municipality and District of Bantul. Multivariate analysis after controlled by gender and energy intake, showed that obese  children who rarely consuming fruits (<7 times/week) (OR=2,24, 95%CI: 1.53-3.28), rarely consuming vegetables (<7 times/week) (OR=2,52, 95%CI: 1,70-3,73), and consuming fruits and vegetables less than 5 servings/day (equivalent to 400 g/day) (OR= 4,59, 95%CI:2,11-10,00) were greater risk for being obesity.Conclusion:Obese children had rarely and less consume of fruits and vegetables than that did in non-obese children at Yogyakarta Municipality and District of Bantul. The children rarely and less consuming fruits and vegetables increased the risk of obesity.KEYWORDS: children obesity, vegetable, fruitABSTRAKLatar Belakang: Indonesia saat ini mengalami masalah gizi ganda, yaitu masalah gizi kurang dan gizi lebih. Kelebihan  gizi atau obesitas pada anak dan remaja apabila tidak diatasi maka berdampak menjadi obesitas pada masa dewasa yang berpotensi mengalami penyakit tidak menular, seperti jantung, hipertensi dan diabetes mellitus. Prevalensi obesitas pada anak di Provinsi Daerah Istimewa Yogyakarta mengalami peningkatan dari tahun ke tahun (1; 2). Obesitas disebabkan ketidakseimbangan antara masukan dengan keluaran energi. Anak cenderung mengkonsumsi padat energi yang berasa manis dan berlemak tinggi serta makanan kurang serat dari buah dan sayur. Beberapa penelitian menunjukkan peningkatan risiko obesitas pada orang yang kurang konsumsi buah dan sayur.Tujuan: Untuk mengetahui perbedaan frekuensi dan jumlah konsumsi buah dan sayur pada anak SD obes dan tidak obes di Kota Yogyakarta dan Kabupaten Bantul serta peran konsumsi buah dan sayur terhadap kejadian obesitas. Metode: Rancangan penelitian ini adalah case-control, 244 kasus (anak obes) dan 244 kontrol (anak tidak obes). Subjek penelitian adalah anak usia 6-12 tahun yang duduk di kelas 1 hingga kelas 5 sekolah dasar di Kota Yogyakarta dan di Kabupaten Bantul. Data identitas diperoleh dari kuesioner terstruktur, sedangkan data frekuensi dan jumlah konsumsi buah dan sayur diperoleh dari semikuantitatif FFQ. Hasilnya kemudian dianalisis menggunakan uji statistik.Hasil: Pada anak SD obes dan tidak obes di Kota Yogyakarta dan Kabupaten Bantul terdapat perbedaan yang signiﬁkan(p<0,05) dalam frekuensi dan jumlah konsumsi buah dan sayur. Hasil analisis multivariat setelah dikontrol dengan jenis kelamin dan asupan energi menunjukkan bahwa anak SD obes yang mengkonsumsi buah jarang (< 7 kali/minggu) (OR=2,24, 95%CI:1,53-3,28), frekuensi konsumsi sayur jarang (<7 kali/minggu) (OR=2,52, 95%CI: 1,70-3,73), jumlah konsumsi buah dan sayur kurang dari 5 porsi/hari atau setara dengan 400 gr/hari (OR=4,59, 95%CI: 2,11-10,00) berisiko lebih besar untuk terjadinya obesitas. Kesimpulan: Anak SD yang obes lebih jarang dan lebih sedikit mengkonsumsi buah dan sayur dibandingkan dengan anak SD yang tidak obes di Kota Yogyakarta dan Kabupaten Bantul. Anak yang jarang dan sedikit mengkonsumsi buah dan sayur dapat meningkatkan risiko terjadinya obesitas.KATA KUNCI: obesitas anak, sayur, buah